2006
DOI: 10.1080/09638230600998904
|View full text |Cite
|
Sign up to set email alerts
|

Relations of social anxiety variables to drinking motives, drinking quantity and frequency, and alcohol-related problems in undergraduates

Abstract: Background: The co-morbidity between social phobia and alcohol disorder is well established. Aims: This study investigated the nature of the relationship between traits associated with these disorders. Method: A total of 157 undergraduate drinkers (112 women; 45 men) completed measures tapping aspects of social phobia (i.e., the Social Avoidance and Distress Scale and the Brief Fear of Negative Evaluation scale) and drinking behavior (i.e., the Drinking Motives Questionnaire -Revised, quantity and frequency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
147
2
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(168 citation statements)
references
References 36 publications
18
147
2
1
Order By: Relevance
“…Similar to the results of the present study, in general, studies conducted so far in the literature report that the fear of negative evaluation varies according to the gender variable (Stewart, Morris, Mellings, & Komar, 2006;Ketra, 2012;Bremser, 2012;Karademir, 2015). Çepikkurt and Coşkun (2010) conducted a study and investigated the social physical anxiety levels of university dancers, and reported that there was a significant difference between the females and males.…”
Section: Discussionsupporting
confidence: 75%
“…Similar to the results of the present study, in general, studies conducted so far in the literature report that the fear of negative evaluation varies according to the gender variable (Stewart, Morris, Mellings, & Komar, 2006;Ketra, 2012;Bremser, 2012;Karademir, 2015). Çepikkurt and Coşkun (2010) conducted a study and investigated the social physical anxiety levels of university dancers, and reported that there was a significant difference between the females and males.…”
Section: Discussionsupporting
confidence: 75%
“…First, data add to prior work (Schry & White, 2013) indicating that HSA undergraduates may experience significantly more frequent alcohol-induced risky sexual behaviors and consequences than LSA undergraduates. Second, the current study adds to a growing corpus of work finding social anxiety to be more related to coping-motivated drinking (Buckner et al, 2006;Ham et al, 2007;Ham, Zamboanga, Bacon, & Garcia, 2009;Lewis et al, 2008;Norberg et al, 2010;Stewart et al, 2006;Terlecki & Buckner, 2015). The current study extends this knowledge base by showing that coping-motivated drinking is related to more frequent alcohol-influenced risky sexual behaviors and consequences among HSA persons.…”
Section: Discussionsupporting
confidence: 63%
“…The literature suggests that social anxiety is related to drinking in situations involving negative affect (Buckner, Eggleston, & Schmidt, 2006;Terlecki & Buckner, 2015) and to more coping-motivated drinking (Blumenthal, Leen-Feldner, Frala, Badour, & Ham, 2010;Buckner & Shah, 2015;Ham, Bonin, & Hope, 2007;Lewis, Hove, Whiteside, Lee, Kirkeby et al, 2008;Norberg, Norton, Olivier, & Zvolensky, 2010;Stewart, Morris, Mellings, & Komar, 2006;Terlecki & Buckner, 2015). Furthermore, drinking to cope with negative affectivity is thought to reinforce regular use of alcohol (Sher & Levenson, 1982), resulting in elevated blood alcohol levels and alcohol tolerance (Weiss & Porrino, 2002), which are symptoms of alcohol use disorder (American Psychiatric Association [APA], 2013).…”
Section: Alcohol-induced Risky Sexual Behavior Among Socially Anxiousmentioning
confidence: 99%
“…Some research suggests strong associations between social anxiety and alcohol use in both adolescents and adults (Buckner et al, 2006;Burke and Stephens, 1999;Stewart et al, 2006). In these studies, social anxiety is seen as a risk factor for the development of problematic alcohol use.…”
Section: Abstract: Objectivementioning
confidence: 99%